2023
DOI: 10.3390/antiox12020365
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of SO2 with an Unripe Grape Extract and Chitosan during Oak Aging: Case Study of a Sangiovese Wine

Abstract: The aim of this study was to evaluate the chemical, microbiological and sensory characteristics of a Sangiovese wine aged in barrique with the addition of an unripe grape extract (UGE) as an alternative to sulfur dioxide. Three samples were considered: control wine (TQ) with free SO2 of approximately 15 mg/L; sample A with chitosan (100 mg/L) and UGE (200 mg/L); and sample B with UGE (400 mg/L). The results achieved in this work demonstrated that the UGE, either alone or in combination with chitosan, was able … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…A recent study has shown that the use of unripe grape extract and chitosan in Sangiovese wine can provide comparable protection against SO 2 . However, more experiments should be carried out in white wines, which are more susceptible to oxidation (Fia et al., 2023).…”
Section: Antioxidant: So2mentioning
confidence: 99%
“…A recent study has shown that the use of unripe grape extract and chitosan in Sangiovese wine can provide comparable protection against SO 2 . However, more experiments should be carried out in white wines, which are more susceptible to oxidation (Fia et al., 2023).…”
Section: Antioxidant: So2mentioning
confidence: 99%
“…Sulfur dioxide (SO 2 ) has played a key role in the wine industry due to its antimicrobial, antioxidant, and antioxidase properties, inhibiting the development of spoilage microorganisms including yeasts, lactic acid bacteria (LAB), and acetic acid bacteria (AAB) [1]; keeping the wine from browning after reacting with hydrogen peroxide [2]; and reducing wine quinones to their phenolic form [3]. However, recent decades have seen concerns raised related to its use in foods due to possible pseudo-allergic reactions associated with its consumption, including dermatitis, rashes, anaphylaxis, and even abdominal pain [4], which has led to limitations on its use in winemaking.…”
Section: Introductionmentioning
confidence: 99%